RURAL EDUCATION PRACTICES IN THE 20TH CENTURY - Hilal BİLMEZ , Derin and ARPACIOĞLU, Ümit (SSD Journal, 2022)
The lack of education in the countryside is one of the biggest problems inherited by the Ottoman Empire to the Republic of Turkiye.The fact that a large part of the population lives in the countryside, that the educational institutions in the countryside provide religious-oriented education and that this education is far from a common system has brought along the education problem. The Republic of Turkiye has been aware of the education problem in the countryside since its establishment and has tried to produce solutions. Before the teacher in the countryside eliminated his/her deficiency, he/she connected all educational institutions to the Ministry of National Education and ensured the teaching unity. As the first concrete step for the Village Teacher problem, village children who can teach were made village teachers for three years with short-term courses. The success achieved here has led to the institutionalization of these courses and first Village Teacher Schools and then Village Institutes have been opened. One of the reasons for the opening of village institutes is to reduce the difference between the city and the village, to develop the village and the villagers, to increase the cultural level of the society and to meet the needs of teachers and other occupational groups in the countryside. The institutes were merged with Primary Schools for severe criticism nearly a decade after opening. In this way, these institutions only started to train teachers again. Primary Teacher Schools have been transformed into higher education institutions over time and have been connected to faculties of education. In the 21st century, various private institutions and organizations produced and implemented projects to support and encourage education in rural areas.